A complex ecosystem: a grounded theory approach to understanding student lending in tertiary education - Muramba, Faith (Graduate School of Business (GSB), 2025)
ABSTRACT Education, including tertiary education, has a valuable role to play in addressing developmental challenges such as poverty, income inequality, unemployment and gender equality. The challenge to providing tertiary education is financing given competing needs on the national fiscus from other sectors such as basic education, healthcare and energy. Student loans are a solution that have been argued to be a more equitable and sustainable form of financing tertiary education but come with their own challenges. An ecosystem lens to tertiary student lending was applied due to the complex combination of economic and social motivations for education, the significant roles played by participants in both the private and public spheres and the financial resources required by student loan programs. By considering the ecosystem and not just an aspect of the student loan market such as default rates, as commonly done in the literature, the results of this study reflect the intricate decision making and multiple agents involved in student loan programs. A qualitative research method was selected as it suited the research question, the textual form of the data and the complex nature of the relationships under investigation in a student lending ecosystem. Applying the grounded theory approach, core categories were identified by a process of abstraction from a representative sample of documentary sources accessed electronically. The conceptual model developed from the core categories, and the insights gained from the literature review were adapted to a scientific framework in order to create a causal loop diagram in the theory building. The scientific framework used in this theory building process is that of archetypes that describe scientifically established generic structures of systems and the associated patterns of behaviour. The final model and theory presented in this study, represents a broad set of stakeholders and highlights the important considerations to improving tertiary student lending. In the theory presented, decisions regarding tertiary student lending are distinctly bounded in two areas – government and non-government, and communication of information between these areas is subject to delays that will hinder efforts to increase loans to students. Students are at the centre of the reinforcing mechanisms supporting loans as they process loan information, availability of loans and expected repayment in the evaluation of their borrowing decisions. Balancing mechanisms to this are centred in government policy as the provision of capital from government has a limit while hidden grants and flexibility in delinquency reduce the expected repayments. The theory predicts stagnant or decreasing levels of loan disbursement if the mechanisms and boundaries above are not addressed and resource limitations removed. To demonstrate practical adequacy, the theory is applied to the National Student Financial Aid Scheme (NSFAS) in South Africa